COMMUNICATION THEORY MEDIA, TECHNOLOGY AND SOCIETY - DAVID HOLMES (sage, 2000)
A theory of communication must be developed in the realm of abstraction. Given that physics has taken this step in the theory of relativity and quantum mechanics, abstraction should not be in itself an objection. N. Luhmann, Art as a Social System, trans. Eva M. Knodt, Stanford: Stanford University Press, 2000, p. 12 What follows is an interdisciplinary communication theory book which sets out the implications of new communications technologies for media studies and the sociology of communication. The cluster of texts which came out over the last decade dealing with computer-mediated communication (CMC), virtual reality and cyberspace has significantly established new theoretical domains of research which have been accepted across a range of disciplines. The current book proposes to integrate this literature in outline and summary form into the corpus of communication studies. In doing so it explores the relationship between media, technology and society. How do media, in their various forms, extend the social, reproduce the social, or substitute for other aspects of social life? Most books dealing with communication and media studies invariably address traditional concerns of content, representation, semiotics and ideology. Whilst including an appreciation of these approaches, the current book makes a contribution to theoretical analysis of media and communications by charting how the emergence of new post-broadcast and interactive forms of communication has provided additional domains of study for communication theory, renovated the older domain of broadcast, and suggested fresh ways of studying these older media. In doing so, this book advances a critique of the ‘second media age’ thesis, which, I argue, has become something of an orthodoxy in much recent literature. It rejects the historical proposition that a second media age of new media, exemplified by the Internet, has overtaken or converged with an older age of broadcast media. Yet at the same time, the value of analytically distinguishing between the most significant architecture that is attributed to the first media age – broadcast – and that which is attributed to the second media age – interactive networks – is upheld. The basic dualism between broadcast and interactivity structures the main themes of the book. To the extent that individuals in media societies experience changes in the means of communication as a ‘second media age’, we are compelled to re-examine the postulated ‘first media age’ in terms of medium or network form rather than simply content or ‘text’. The sense in which this distinction is made should not be confused with questions of form versus the content of narrative, where content is what a text says, and the form is how it says it. Rather, a non-textual distinction is being made here. In doing so, a sociological appreciation of broadcast can be arrived at rather than a media studies or cultural studies perspective, which is invariably grounded exclusively in either behaviourist or linguistically centred approaches to analysis. However, insofar as this book is ‘sociological’, sociology is not being opposed to communication and media studies; on the contrary, a central argument of the book is that emergence of new communication environments has more or less forced traditional media and communication studies to be sociological. For this reason the current volume is very interdisciplinary (between communication, media and sociology), but this has less to do with the perspective adopted than with changes in how media are experienced. These recent changes in media infrastructure have necessitated a shift in the order in which communication theory is treated. For example, information theory, which often prefigures semiotic analysis of media, is introduced in the current textbook as instructive for the second media age, where it more appropriately belongs with analyses of the Internet. In fact, in seeing just how relevant information theory is to CMC rather than broadcast, it is surprising how significantly it came to figure in studies of broadcast in the first place. At the same time, the book tries to incorporate most of the traditions of twentieth-century communication theory in order to locate their relevance to studying the sociological complexities of contemporary convergent communications.